Effect of Treatment with 3-Hydroxy-3-methylglutaryl Coenzyme A Reductase Inhibitors on Serum Coenzyme Q10 in Diabetic Patients - Miyake, Yutaka; Shouzu, Akira; Nishikawa, Mitsushige; Yonemoto, Toshinaga; Shimizu, Hidekazu; Omoto, Seitaro; Hayakawa, Takassh; Inada, Mitsuo (Arzneimittelforschung, 1999)
Serum coenzyme Q10 (CoQ10: 2-(3,7,11,15,19,23,27,31,35,39-decamethyl-2,6,10,14,18,22,26, 30,34,38-tetracontadecaenyl)-5,6-dimethoxy-3-methyl-1,4-benzoquinone, CAS 303-98-0) and cholesterol levels were measured to assess the effect of cholesterol-lowering therapy in patients with non-insulin-dependent diabetes mellitus (NIDDM). Twenty healthy volunteers, 97 NIDDM patients and 2 patients with familial hypercholesterolemia were studied. None had overt heart failure or any other heart disease. Mean serum CoQ10 concentrations were significantly (p < 0.01) lower in diabetic patients with normal serum cholesterol concentrations, either with or without administration of 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (HMG-CoA RIs) including simvastatin (normal: 0.91 ± 0.26 (mean ± SD) 1−1; diabetic with HMG-CoA RI: 0.63 ± 0.19; diabetic without HMG-CoA RI: 0.66 ± 0.21). CoQ10 concentrations were higher (1.37 ± 0.48, p < 0.001) in diabetic patients with hypercholesterolemia. Simvastatin or low density lipoprotein apheresis decreased serum CoQ10 concentrations along with decreasing serum cholesterol. Oral CoQ10 supplementation in diabetic patients receiving HMG-CoA RI significantly (p < 0.001) increased serum CoQ10 from 0.81 ± 0.24 to 1.47 ± 0.44 l−1, without affecting cholesterol levels. It significantly (p < 0.03) decreased cardiothoracic ratios from 51.4 ± 5.1 to 49.2 ± 4.7%. In conclusion, serum CoQ10 levels in NIDDM patients are decreased and may be associated with subclinical diabetic cardiomyopathy reversible by CoQ10 supplementation.
Keywords: CAS 303-98-0; Coenzyme Q10; Diabetes mellitus, non-insulin-dependent; 3-Hydroxy-3-methylglutaryl coenzyme A reductase, inhibitors; Pravastatin; Simvastatin